Analysis of Financial Distress with The Altman, Springate, Zmijewski, Grover, and Taffler Models in The Consumer Cyclicals Sector in The Covid-19 Pandemic - Ikwan Mustafa; Dien Noviany Rahmatika; Roberto Akyuwen (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
The Covid-19 pandemic has changed the order of the world economy, which allows for financial distress (financial distress) in a company. This study aims to determine the financial distress condition of companies in the consumer cyclicals sector in 2018-2021 using the Altman, Springate, Zmijewski, Grover, and Taffler models. In addition, to find out the difference in financial distress before the Covid-19 pandemic occurred with during the Covid-19 pandemic and the level of accuracy of each model used. This research is a type of quantitative research using a purposive sampling technique so 66 samples were selected. The data used is secondary data, in the form of financial statements for 2018-2021. The results of the study show that there are differences in each of the financial distress prediction models used. The results of the average difference test (paired simple T-test) from the prediction model used only the Altman model which shows no difference in financial distress conditions before the Covid-19 pandemic occurred during the Covid-19 pandemic. Meanwhile, the Springate, Zmijewski, Grover, and Taffler models show differences in financial distress conditions. The accuracy level of the Altman model is 87.88%, Taffler 83.71%, Grover 74.24%, Springate 73.48%, and Zmijewski 68.18%. So it can be concluded that the Altman model is the model with the highest level of accuracy in predicting financial distress in the consumer cyclicals sector of companies.